Analisis Rasio Keuangan terhadap Kualitas Laba Perusahaan Makanan & Minuman yang Terdaftar di BEI - Septiana Putri Hargyanti; Yuli Chomsatu (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2021)
Abstract : This study aims to determine the effect of company size, profitability, liquidity, leverage, and company values ​​on earnings quality. The population in this study is the Food and Beverage company on the Indonesia Stock Exchange (IDX) in 2015-2018. The sample was selected from the purposive sampling method and obtained a sample of 12 companies from several criteria. The data source is secondary data from the website (www.idx.co.id). This research uses multiple linear regression analysis with the help of SPSS version 20. The results of this research show that company size has an influence on earnings quality. While profitability, liquidity, leverage, and firm value do not have an influence on earnings quality. The results of this research are expected to be an additional consideration for company management in the process of deciding taxation policies. And can be additional information for users of financial statements for consideration of investment decisions ".